Fast living cationic polymerization of isobutyl vinyl ether tailored by single nucleophile in microflow system. (April 2019) - Xie, Dan; Lu, Yangcheng
Graphical abstract: Highlights: Simplify initiation system for living IBVE by using single nucleophile successfully. Assure uniform and well controlled active species by using single nucleophile. Enable even faster living cationic polymerization tailored by single nucleophile. Verify correspondence between binding energy and living characteristic in single nucleophile selection. Abstract: The application of living cationic polymerization suffers from complex and costly additives as well as low productivity. In this work, we attempted to develop fast living cationic polymerization of isobutyl vinyl ether (IBVE) tailored by reduced single nucleophile in microflow system. Living polymers were successful obtained for the systems of IBVE-HCl/FeCl3 ·DO/DO and IBVE-HCl/FeCl3 ·DOL/DOL. The kinetic behavior of IBVE polymerizations at various concentration of nucleophiles revealed that a microflow system could afford living characteristics as the time to reach 50% conversion (t1/2 ) is as short as 0.22 s. Using single nucleophile can avoid the negative cooperativity of multi-nucleophiles in stabilizing carbocations, allow the decrement of nucleophile, and enhance the controllability of polymerization process. DFT simulations indicate that only the nucleophile with relatively higher binding energy could endow the system with living characteristic. From this point of view, the addition of other nucleophile with relatively lower binding energy may have no positive effect. These recognitions are meaningful for the development of living cationic polymerization towards commercial application.